Functional identification of the prnABCD operon and its regulation in Serratia plymuthica - Liu, Xiaoguang; Yu, Xiaoli; Yang, Yang; Heeb, Stephan; Gao, Shao; Chan, Kok Gan; Cámara, Miguel; Gao, Kexiang (Springer, 2018)
The antibiotic pyrrolnitrin (PRN) is a tryptophan-derived secondary metabolite that plays an important role in the biocontrol of plant diseases due to its broad-spectrum of antimicrobial activities. The PRN biosynthetic gene cluster remains to be characterised in Serratia plymuthica, though it is highly conserved in PRN-producing bacteria. To better understand PRN biosynthesis and its regulation in Serratia, the prnABCD operon from S. plymuthica G3 was cloned, sequenced and expressed in Escherichia coli DH5α. Furthermore, an engineered strain prnind which is a conditional mutant of G3 prnABCD under the control of the Ptac promoter was constructed. This mutant was able to overproduce PRN with isopropylthiogalactoside (IPTG) induction by overexpressing prnABCD, whilst behaving as a conditional mutant of G3 prnABCD in the absence of IPTG. These results confirmed that prnABCD is responsible for PRN biosynthesis in strain G3. Further experiments involving lux-/dsRed-based promoter fusions, combined with site-directed mutagenesis of the putative σS extended -10 region in the prnA promoter, and liquid chromatography-mass spectrometry (LC-MS) analysis extended our previous knowledge about G3, revealing that quorum sensing (QS) regulates PRN biosynthesis through cross talk with RpoS, which may directly activated prnABCD transcription. These findings suggest that PRN in S. plymuthica G3 is produced in a tightly controlled manner, and has diverse functions, such as modulation of cell motility, in addition to antimicrobial activities. Meanwhile, the construction of inducible mutants could be a powerful tool to improve PRN production, beyond its potential use for the investigation of the biological function of PRN.